Demographic rates and diversity vary with tree stature and ontogenetic stage in an African tropical rainforest - Moses B. Libalah; Sabrina E. Russo; George B. Chuyong; Duncan Thomas; David Kenfack (Ecosphere)
Abstract The vertical gradient of light in closed‐canopy forests selects for trees with different adult statures, but our understanding of how stature affects forest diversity and demography is unclear. In a species‐rich rainforest in Cameroon, we quantified the contributions of four growth forms of increasing adult stature (treelet, understory, canopy, emergent species) to forest structure and diversity, and investigated variation in life history trade‐offs across growth forms. Treelets had the highest stem density, contributed the most to forest diversity, and diverged from larger statured species in terms of demographic trade‐offs. Growth rates were slower for smaller statured than for larger statured species, and at the adult stage, treelets had significantly lower mortality than other growth forms. We observed significant interspecific trade‐off relationships between staure and demographic rates that often differed between growth forms. Recruitment rate strongly declined with adult stature for all growth forms, but recruitment per reproductive adult declined only for emergents. While we observed a significant growth‐mortality trade‐off across all species, the trade‐off was similar across growth forms. Smaller statured species in our study are not light‐demanding but rather treelet and understory species that live entirely in the shaded understory. Differences in how historical biogeography has shaped species pools may ultimately cause variation in how adult stature contributes to tropical forest diversity.